2020
DOI: 10.3390/joitmc6040195
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Innovation, Open Innovation Dynamics and Competitive Advantage of Medium and Large-Sized Firms

Abstract: The present research investigates the contribution of environmental innovation to firms’ competitive advantage through the case of medium and large-sized firms operating in Greece. Due to the growing trend of environmental innovation in Greece and a consequent increase in the research interest, this paper fills the existing gap in the relevant literature as there is not enough evidence concerning Greek firms’ environmental innovation practices. To meet the research goal, a questionnaire was distributed to 892 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 114 publications
(238 reference statements)
2
62
0
12
Order By: Relevance
“…Innovation is the process of generating new solutions based on the new knowledge that taking the form of product or process innovation [57,58]. The open innovation surpasses the internal boundaries of a company to include all the collaborations with people and external organizations to the company [59].…”
Section: Open Innovationmentioning
confidence: 99%
“…Innovation is the process of generating new solutions based on the new knowledge that taking the form of product or process innovation [57,58]. The open innovation surpasses the internal boundaries of a company to include all the collaborations with people and external organizations to the company [59].…”
Section: Open Innovationmentioning
confidence: 99%
“…Companies open themselves up to the outside world to innovate by cultivating an authentic culture of open innovation [75]. They may benefit from incorporating outside expertise from an open-innovation perspective and making the company boundaries permeable [76][77][78][79]. For example, by collaborating with customers and suppliers, companies can gain various environmental advantages from their innovations [15].…”
Section: Discussion: Green Innovation and Open Innovation In The Envmentioning
confidence: 99%
“…Over the past two decades, the study of Adams et al [11] showed that the foundations of sustainable business practice began to be established, as reflected in many prominent environmentally and socially concerned platforms and initiatives for a business being set up and created. The research results of Skordoulis et al [52] revealed a moderate level of environmental innovation implemented in firms. The most implemented practices were the ISO 14001 management systems and the toxic substances usage reduction.…”
Section: Further Suggestionsmentioning
confidence: 95%
“…Previous studies of Bright and Boks [9], Rio et al [26], and Piekarski et al [51] addressed a crucial requirement of collaboration between designers and LCA experts to foster the systematically integrated environmental aspects into the design process. The need of adhering to a cross-industry innovation process can be emphasized to improve the performance of environmental innovation, such as new business models, new ventures and spin-offs, and new markets of technology application [52]. New design proposals at the level of system innovation can lead to system, institutional, and societal changes.…”
Section: Opportunitiesmentioning
confidence: 99%